IKAN MAS ARSIK SEBAGAI MEDIA PENGENALAN BUDAYA DALAM PEMBELAJARAN BIPA - Ririn Fresentia Natalia Br Pandia; Dian Syahfitri; Fretty Sarima Nainggolan; Dia Pika Marlina Br Ginting; Putu Dewi Merlyna (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The importance of integrating local cultural elements in the Indonesian Language for Foreign Speakers (BIPA) teaching program to strengthen cross-cultural communicative competence is the background to writing this article. Field operational problems trigger the limited availability of contextual teaching material drafts which result in obstacles to sociocultural understanding for international learners when learning the language. The main focus of this scientific study is to explore the symbolic meaning of the local wisdom of the traditional dish dekke na niarsik or Arsik Goldfish in Toba Batak traditional wedding ceremonies while formulating a draft for its media implementation. The steps of this descriptive qualitative research are operated using the semiotic theory of Charles Sanders Peirce which dissects the triadic correlation of signs between representamen, objects, and interpretants. Data collection procedures are collected in a structured manner through literature studies, participant observation, and draft documentation of cultural records. Empirical research findings reveal that this traditional culinary represents a draft of symbolic meaning for blessings, fertility of lineages, and household harmony. The utilization of these philosophical values ​​is then integrated into the draft of an interactive digital platform based on games using Kahoot media. The main conclusion confirms that the hybridization of culinary wisdom and digital media has proven to be very reliable in reducing class boredom and significantly increasing the learning motivation of foreign speakers. ABSTRAK Pentingnya integrasi unsur kebudayaan lokal dalam program pengajaran Bahasa Indonesia bagi Penutur Asing (BIPA) guna memperkuat kompetensi komunikatif lintas budaya melatarbelakangi penulisan artikel ini. Masalah operasional lapangan memicu keterbatasan ketersediaan draf materi ajar kontekstual yang berakibat pada hambatan pemahaman sosiokultural bagi para pemelajar internasional saat mempelajari bahasa. Fokus utama kajian ilmiah ini adalah mengeksplorasi makna simbolik kearifan lokal hidangan tradisional dekke na niarsik atau Ikan Mas Arsik pada upacara pernikahan adat Batak Toba sekaligus merumuskan draf implementasi medianya. Langkah-langkah penelitian kualitatif deskriptif ini dioperasikan menggunakan landasan teori semiotika Charles Sanders Peirce yang membedah korelasi tanda triadik antara representamen, objek, dan interpretant. Prosedur pengumpulan data dihimpun secara terstruktur via studi pustaka, observasi partisipatif, serta draf dokumentasi rekam budaya. Temuan penelitian secara empiris menyingkap bahwa kuliner tradisional ini merepresentasikan draf makna simbolis atas pemberkatan, kesuburan garis keturunan, serta keharmonisan rumah tangga. Pemanfaatan nilai filosofis tersebut kemudian diintegrasikan ke dalam draf platform digital interaktif berbasis permainan menggunakan media Kahoot. Simpulan utama menegaskan bahwa hibridasi kearifan kuliner dan media digital terbukti sangat andal dalam mereduksi kejenuhan kelas serta meningkatkan motivasi belajar penutur asing secara signifikan.